Model Matematika Penyebaran Penyakit Herpes Genital dengan Vaksinasi - Aziza Masli; Media Rosha (UNIVERSITAS NEGERI PADANG, 2020)
Abstract — Genital herpes is an infectious disease that can be transmitted and caused by Herpes Simplex Virus type 2 (HSV-2). According to WHO, genital herpes caused by HSV-2 is a global issue and it is estimated that 491 million people in the world are living with HSV-2 infection in 2016. Health observers are looking for solutions to the spread of genital herpes by developing prophylactic protection vaccines. In this research, a mathematical model of the spread of genital herpes with vaccination will be sought. The purpose of this study is to learn how to use vaccination against the spread of genital herpes. This study is a basic study using descriptive method. This method is done by analyzing theories relating to the problem. The study began by determining the variables, parameters, and assumptions that related to the spread of genital herpes with vaccination. The results of the analysis show that high rates of disease transmission can lead to diseas outbreak. In addition, increasing the precentage of successful vaccines can reduce the spread of genital herpes so that outbreaks not occur. Keywords — mathematics model, genital herpes, vaccination.